The Effect Of Team Properties On Team’s Performance As Perceived By Team Members Of Multinational Manufacturing Companies In Penang - Fabeil, Noor Fzlinda (2004)
Teams have become increasingly popular in firms of all sizes and industries. Managers believe that teams often provide better outcomes than individual, but high performance teams are rarity due to failure of organization in identifying the critical criteria that influence performance of a team.